Commodity Markets Outlook, January 2015 - World Bank Group (Washington, DC, 2015)
Broad-based commodity price declines occurred in the second half of 2014. Crude oil prices declined the most, down 55 percent to $47 per bbl (barrel) in early January, from a high of $115 per bbl in late-June 2014, bringing an end to a four-year period of high and stable prices. The oil price drop is the third-largest seven-month decline of the past three decades - only the 67 percent drop from November 1985 to March 1986 and the 75 percent drop from July to December 2008 were larger. Agricultural, metal, and precious metal prices weakened as well, down by 6, 8, and 9 percent, respectively, in 2014 fourth quarter (Q4) from the previous quarter. Ample supplies, disappointing global growth prospects, and an appreciating Unites States (U.S.) dollar have all weighed on prices. In oil markets, a sequence of (upward) supply and (downward) demand revisions, along with organization of petroleum exporting countries (OPEC's) abandoning of supply management, have played a pivotal role in the price collapse.